(untitled) - Qureshi, Hasnain (Darya Ganj, New Delhi, 2006)
Contents of material: Concept and evolution. Rapid growth. Practical aspects. Social role. Plans and schemes. Laws for functionning. Role in education. Acadamic libraries. Popular libraries. Reference libraries. Special libraries. The personnel. Inter-library contacts. Models abroad.
Keywords: Library science,Libraries